Characterization and Photocatalytic Activity of Nano-TiO2 Doped with Iron and Niobium for Turquoise Blue Dye Removal - Nhat Minh Doan; Carl Renan Estrellan; Anton Purnomo; Anton Gallardo; Chris Salim; Hirofumi Hinode (ASEAN Journal of Chemical Engineering, 2012)
The nano-TiO2 photocatalysts doped with Iron and Niobium for dye wastewater treatment were prepared by temperature-controlled sol-gel method. The effects of these dopants on the physical and chemical properties of TiO2 were compared with the commercially available Degussa TiO2 P25. Among these characteristics are crystalline size, the presence of absolute anatase phase, band gap energy and specific surface area. The characterization data were correlated to photocatalytic activities using Turquoise blue dye (TBD) as model pollutant. Single doping (with Nb) and co-doping (Fe and Nb) catalyst reached complete decolorization within 2.5 hours and 3 hours. In addition, their kinetic reaction rate constants of apparent first-order model are 0.0258 min-1 and 0.0225 min-1, respectively. The presence of Nb as traps is considered to play a crucial key in enhancing the photocatalytic activity.